Pengaruh Metode Ekstraksi Sonikasi terhadap Total Flavonoid Content dari Daun Pare (Momordica charantia L.) - Nur Octaviana; Hesty Parbuntari (MASALIQ, 2025)
The use of medicinal plants in Indonesia is still largely based on traditional knowledge passed down through generations, often lacking sufficient scientific validation. Momordica charantia L., a plant from the Cucurbitaceae family, is widely recognized in traditional medicine for its flavonoid content found in the leaves, which exhibits antioxidant, antidiabetic, antirheumatic, and antimicrobial properties. This study aims to determine the effect of sonication on the total flavonoid content of pare (bitter melon) leaves. Extraction was carried out using a sonicator for 60 minutes at 40 °C, with a power of 50 W and a frequency of 40 kHz. The filtrate obtained from the filtration process was then evaporated using a rotary evaporator with 70% ethanol as the solvent. The total flavonoid content was determined using a UV-Vis spectrophotometer at a maximum wavelength of 431 nm. The results showed that the sonication method produced a total flavonoid content of 159.42 mg QE/g, which is considered high. These findings indicate that sonication is a fast, efficient, and environmentally friendly extraction method for obtaining flavonoid compounds from Momordica charantia leaves. This study contributes scientifically to the development of modern green technology-based extraction methods for the utilization of local medicinal plants.